Aplikasi Toko Sembako Online Berbasis Web Codeigniter (Study Case Pt Jtrust Olympindo Multifinance) - Ariandi Nugroho; Dian Nugraha; Untung Suprihadi; Safira Faizah; Dewi Rahmasari; Rizki Adrian Firdaus (STMIK IKMI Cirebon, 2021)
The outbreak of the covid-19 virus has caused many listing and funding companies to go bankrupt. J-trus group is one of the companies that has experienced the impact of covid 19, so that the company is able to survive, the company is looking for other ways to get additional income, namely by expanding the sale of basic necessities online, here the author provides a solution using a web-based application to realize this the. So the purpose of this paper is to design and build a PHP-based application with the Codeignither framework. The method uses the waterfall and the database uses a MYSQL database. The design includes Use Case Diagrams, Activity Diagrams, class diagrams. Testing the application with the Black Box testing method, functionally has been declared successful. And based on the test results using the System Usability Scale (SUS), a score of 71 has been obtained with a value above the average so that it can be accepted by users